Rutas de descarbonización profunda en América Latina: Desafíos y oportunidades - Christopher Bataille; Henri Waisman; Adrien Vogt-Schilb; Marcela Jaramillo; Ricardo Delgado; Ricardo Argüello; Leon Clarke; Thomas Wild; Francisco Lallana; Gonzalo Bravo; Gaëlle LeTreut; Gustavo Nadal; et al. (Inter-American Development Bank (IDB), 2020)
– This synthesis paper presents the objectives, approach and cross-cutting results of the Latin American Deep Decarbonization Pathways project (DDPLAC). It synthesizes and compares detailed national and sectoral deep decarbonization pathways (DDPs) to 2050 compatible with the Paris Agreement objectives and domestic development priorities in Argentina, Colombia, Costa Rica, Ecuador, Mexico and Peru. The first five countries analysed in detail the energy system and agriculture, forestry and land use (AFOLU) at a high level, while Peru focussed on a detailed analysis of AFOLU given its predominance in its GHG emissions. While economy-wide results were produced, this paper focuses on the electricity, passenger transport, and AFOLU results because of their current emissions, potential to grow, and identification of successful strategies for decarbonization (e.g. switching to clean electricity and switching to other net- zero fuels across the economy; urban planning, mode shifting, and electrification in passenger transport; and intensive sustainable agriculture, assignment of land use rights and their enforcement and afforestation in AFOLU). It also highlights where significant emissions remain in 2050, notably in industry, AFOLU, freight, and oil and gas production, all areas for future research. It also derives insights for the design of domestic policy packages and identifies priorities for international cooperation. This analysis provides critical information for Long-Term Strategies, Nationally Determined Contributions and Global Stocktaking in the context of the Paris Agreement.
Keywords: Q54; 330; Decarbonization; Decarbonization Pathways; Development; Energy; AFOLU